Green synthesis and biological evaluation of novel 5-fluorouracil derivatives as potent anticancer agents - Farhat Jubeen; Aisha Liaqat; Misbah Sultan; Sania Zafar Iqbal; Imran Sajid; Farooq Sher (Elsevier, 2019)
This study reports the formation of 5-FU co-crystals with four different pharmacologically safe co-formers; Urea, Thiourea, Acetanilide and Aspirin using methanol as a solvent. Two fabrication schemes were followed i.e., solid-state grinding protocol, in which API and co-formers were mixed through vigorous grinding while in the other method separate solutions of both the components were made and mixed together. The adopted approaches offer easy fabrication protocols, no temperature maintenance requirements, no need of expensive solvents, hardly available apparatus, isolation and purification of the desired products. In addition, there is no byproducts formation, In fact, a phenomenon embracing the requirements of green synthesis. Through FTIR analysis; for API the NH absorption frequency was recorded at 3409.02 cm−1 and that of CO was observed at 1647.77 cm−1. These characteristics peaks of 5-FU were significantly shifted and recorded at 3499.40 cm−1 and 1649.62 cm−1 for 5-FU-Ac (3B) and 3496.39 cm−1 and 1659.30 cm−1 for 5-FU-As (4B) co-crystals for NH and CO groups respectively. The structural differences between API and co-crystals were further confirmed through PXRD analysis. The characteristic peak of 5-FU at 2θ = 28.79918o was significantly shifted in the graphs of co-crystals not only in position but also with respect to intensity and FWHM values. In addition, new peaks were also recorded in all the spectra of co-formers confirming the structural differences between API and co-formers. In addition, percent growth inhibition was also observed by all the co-crystals through MTT assay against HCT 116 colorectal cell lines in vitro. At four different concentrations; 25, 50, 100 and 200 µg/mL, slightly different trends of the effectiveness of API and co-crystals were observed. However; among all the co-crystal forms, 5-FU-thiourea co-crystals obtained through solution method (2B) proved to be the most effective growth inhibitor at all the four above mentioned concentrations. Keywords: 5-Fluorouracil, Co-crystals, Green synthesis, Supramolecular interactions, Grinding and solution method